2015
DOI: 10.4236/ojpsych.2015.52020
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Neurofeedback Therapy in Craving of Methamphetamine Use

Abstract: Introduction: Relapse in methamphetamine dependency is one of the most difficult parts to treat. Therefore treatment of craving for usage is one of the essential sections of treatment in methamphetamine dependency (addiction). This study evaluates the effect of neurofeedback therapy on craving for use. Methods: In this study 20 male patient with methamphetamine dependency who diagnosed on the basis of DSM-V were selected. None of the patients had any psychiatric and neurologic disorder except addiction of meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…Our findings showed the effectiveness of LZNFB and cognitive rehabilitation treatments in decreasing craving and attentional bias to drug cues and improving the well-being that are consistent with previous studies (Begh et al, 2013;Campanella, 2016;Cox et al, 2014;Dehghani-Arani, Rostami, & Nadali, 2013;Fals-Stewart & Lam, 2010;Hashemian, 2015;Heidari, Taremian, & Khalatbari, 2017;Passini, Watson, Dehnel, Herder, & Watkins, 1977;E. G. Peniston & Kulkosky, 1989;Potenza et al, 2011;Ross, 2013;Saxby & Peniston, 1995;Schoenmakers et al, 2010;Scott, Kaiser, Othmer, & Sideroff, 2005;Skjaervø, 2010;Taremian, 2014;Robert W Thatcher, 2010;van Hemel-Ruiter et al, 2016;Wiers et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings showed the effectiveness of LZNFB and cognitive rehabilitation treatments in decreasing craving and attentional bias to drug cues and improving the well-being that are consistent with previous studies (Begh et al, 2013;Campanella, 2016;Cox et al, 2014;Dehghani-Arani, Rostami, & Nadali, 2013;Fals-Stewart & Lam, 2010;Hashemian, 2015;Heidari, Taremian, & Khalatbari, 2017;Passini, Watson, Dehnel, Herder, & Watkins, 1977;E. G. Peniston & Kulkosky, 1989;Potenza et al, 2011;Ross, 2013;Saxby & Peniston, 1995;Schoenmakers et al, 2010;Scott, Kaiser, Othmer, & Sideroff, 2005;Skjaervø, 2010;Taremian, 2014;Robert W Thatcher, 2010;van Hemel-Ruiter et al, 2016;Wiers et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Similar to our findings, some studies on alcohol dependence patients by Passini et al Bodehnamer & Callaway, Burkett et al Raymond et al established progressions via comparing the treatment and control groups. Scott et al concluded that neurofeedback treatment enhanced psychological health in mixed substance addicts (Bodenhamer-Davis & Callaway, 2004;Burkett, Cummins, Dickson, & Skolnick, 2004;Hashemian, 2015;Passini et al, 1977;E. Peniston, 1994;E.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 5, neurofeedback training reduced the total scores of food craving in comparison with the control group. These findings are in accordance with the findings obtained by Saxby and Pension (1995), Scott et al, (2005), Hashemian (2015), Rostami and Dehghani-Arani (2015), Dehghani et al, (2008), Imperatori et al (2017). In this study, neurofeedback training reduced craving in the experimental group.…”
Section: Discussionsupporting
confidence: 93%
“…The results showed that neurofeedback intervention reduced craving and tendency to use opioid, and increased general health scores in comparison with the control group. Hashemian (2015) showed the positive effect of neurofeedback on reducing the craving for meta-amphetamine.…”
Section: Introductionmentioning
confidence: 99%